HIV-1-mother-to-child transmission and associated characteristics in a public maternity unit in Presidente Prudente, Brazil - Prestes-Carneiro, Luiz Euribel; Spir, Patrícia Rodrigues Naufal; Ribeiro, Armênio Alcântara; Gonçalves, Vera Lúcia Maria Alves (Revista do Instituto de Medicina Tropical de São Paulo, 2012)
In children, vertical transmission is the main form of HIV infection. Our aim was to determine the prevalence of HIV-1 vertical transmission in mother-infant pairs in a public maternity ward in Presidente Prudente, SP. Additionally; we sought to identify characteristics associated with this form of transmission. The files of 86 HIV-1-infected mothers and their newborns referred to a Public Hospital from March 2002 to March 2007 were analyzed. The HIV-1-RNA viral load of the newborns was determined by bDNA. The HIV-1 vertical-transmission rate was 4.6%. Children that were born in the pre-term period and breastfed were at a higher risk of HIV-1 infection (p = 0.005 and p = 0.017 respectively) than children born at term and not breastfed. Prophylactic therapy with zidovudine after birth for newborns was associated with a lower risk of infection (p = 0.003). The number of newborns weighing < 2,500 g was significantly higher for infected children (p = 0.008) than for non-infected newborns. About 22.9% of mothers did not know the HIV-1 status of their newborns eight months after delivery. The study suggests that it is necessary to increase the identification of HIV-1 infection in pregnant women and their newborns as well as to offer and explain the benefits of ARV prophylaxis.